Synthesis and screening of new maleimide derivatives as potential anti-tubercular agents - Saroj Kumar Sahooa, Kurre Purna Nagasreeb, Jamullamudi Risy Namrathab, Pemmadi Raghuveer Varmab, Muthyala Murali Krishna Kumarb (Journal of Applied Pharmaceutical Science, 2015)
In the present investigation a series of new maleimide derivatives were synthesized by reacting different anilines with maleic anhydride in presence of acetic anhydride and sodium acetate. The synthesized compounds were identified by using IR, 1H NMR and mass spectral data analysis. The preliminary in vitro antimicrobial activity was studied against S. aureus, E. coli and A. niger. Further, the synthesized compounds (PA1-PA15) were subjected to in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv using MABA method. The compounds PA4 (MIC 6.25 µg/ml), PA8 (MIC 3.125 µg/ml), PA14 (MIC 3.125 µg/ml) showed significant inhibitory activity against M. tuberculosis H37Rv.
Keywords: Maleimide, antitubercular, 3,4-diarylpyrrole, denigrin, tuberculosis.